Implementasi Penerapan Green Accounting, Kinerja Lingkungan, dan Human Capital Terhadap Profitabilitas - Nur Via Indrawati; Banu Witono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The research aims to analyze the influence of green accounting, environmental performance and human capital on the profitability of primary consumption companies listed on the Indonesia Stock Exchange (BEI) in 2020-2023. The type of research used is quantitative research with a causative approach, to analyze the relationship between variables. The selected population is all consumer non cyclicals companies listed on the Indonesian Stock Exchange. Obtaining samples using purposive sampling, based on several criteria according to provisions. Secondary data was obtained through annual financial reports, annual reports and sustainability reports sourced from www.idx.co.id as well as the company's official website. The results obtained state that green accounting and human capital have a significant effect on company profitability, while environmental performance does not have a significant effect on profitability. A limitation of the research is that several companies in the primary consumption sector did not publish data regarding their complete financial reports and annual reports for the 2020-2023 period. It is recommended that further research expand the population and research sample and extend the observation period.